Recent advances in materials and design of electrochemically rechargeable zinc – air batteries - Chen, Xuncai (2020)
The century-old zinc-air (Zn-air) battery concept has been revived in the last decade due to its high theoretical energy density, environmental-friendliness, affordability, and safety. Particularly, electrically rechargeable Zn-air battery technologies are of great importance for bulk applications like electric vehicles, grid management, and portable electronic devices. Nevertheless, Zn-air batteries are still not competitive enough to realize widespread practical adoption because of issues in efficiency, durability, and cycle life. Here, following an introduction to the fundamentals and performance testing techniques, the latest research progress related to electrically rechargeable Zn-air batteries is compiled, particularly new key findings in the last five years (2013-2018). The strategies concerning the development of Zn and air electrodes are in focus. The design of other battery components, namely electrolytes and separators are also discussed. Poor performance of O2 electrocatalysts and the lack of the long-term stability of Zn electrodes and electrolytes remain major challenges. Finally, recommendations regarding the testing routines and materials design are provided. It is hoped that this up-to-date account will help to shape the future research activities toward the development of practical electrically rechargeable Zn-air batteries with extended lifetime and superior performance.